2017
DOI: 10.1371/journal.pone.0188033
|View full text |Cite
|
Sign up to set email alerts
|

A multi-paradigm framework to assess the impacts of climate change on end-use energy demand

Abstract: Projecting the long-term trends in energy demand is an increasingly complex endeavor due to the uncertain emerging changes in factors such as climate and policy. The existing energy-economy paradigms used to characterize the long-term trends in the energy sector do not adequately account for climate variability and change. In this paper, we propose a multi-paradigm framework for estimating the climate sensitivity of end-use energy demand that can easily be integrated with the existing energy-economy models. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…Specifically, unanticipated higher demand for space conditioning and refrigeration during heat waves has led to rolling outages with serious socio-economic and public health consequences [7][8][9][10][11][12] . In light of the expected increase in frequency and intensity of climate extremes 3 , climate-induced outages are an increasing risk to the resilient operation of the electric power infrastructure [13][14][15][16][17] .…”
mentioning
confidence: 99%
“…Specifically, unanticipated higher demand for space conditioning and refrigeration during heat waves has led to rolling outages with serious socio-economic and public health consequences [7][8][9][10][11][12] . In light of the expected increase in frequency and intensity of climate extremes 3 , climate-induced outages are an increasing risk to the resilient operation of the electric power infrastructure [13][14][15][16][17] .…”
mentioning
confidence: 99%
“…This will continue until a certain number of iterations has been completed, at which point the weighted predictions will be combined as a final model. This algorithm has been used in a variety of predictive applications, ranging from psychological well-being [22] to infrastructure resilience [23]. A more detailed discussion on the algorithm can be found in Miller et al [22]…”
Section: Algorithm Descriptionmentioning
confidence: 99%
“…In this study, there were two response variables: residential electricity use and residential water use, both normalized by the number of customers served, and 8 meteorological and climatic predictors. There was a focus on variables that are easily measured by meteorological stations because of the availability of such data, as well as the results of previous studies, which showed the importance of meteorological variables on water and electricity demand [32,33,23,34]. Similarly, it has been shown that the El Niño/Southern Oscillation plays an important role in affecting hydroclimatic processes across the US, and reservoir levels in particular [35], and thus making it an important variable to include in the analysis of residential water use.…”
Section: Data Descriptionmentioning
confidence: 99%
“…heating and cooling systems in buildings to large-scale electricity generation infrastructure). For this report, existing research on Indiana's future energy demand and supply based on projected fuel prices and growth rates (Lu 2015) was used in conjunction with projected energy demand and supply shifts in the commercial and residential sectors due to climate change from the statewide Bayesian analysis (Nateghi and Mukherjee 2017).…”
Section: Energy Demand and Extreme Heatmentioning
confidence: 99%